Pasal 1157 Ayat 2 KUH Perdata sebagai Dasar Jaminan Biaya-Biaya Tak Terduga yang Timbul Akibat Menggadaikan Barang Bergerak - Fajar Andika Pratama; Nadia Isna Putri; Ananda Althof Samudra; Eti Mul Erowati (Majelis: Jurnal Hukum Indonesia, 2025)
Pawn is one of the property rights obtained by a person who receives the goods—who provides credit—on a movable and tangible item that is handed over to him by a person who is in debt or by another person on his behalf. Pawning is a common phenomenon in many countries, especially in Indonesia. The regulations related to pawn are determined in the Civil Code, especially in Article 1150 of the Civil Code, and are further regulated in various additional articles in the Civil Code. Pawn requires the existence of two or more parties who are related to each other and agree to make a binding agreement with a certain period of time to receive and provide guarantees to an entity in return for a certain amount of money or other goods, which must then be returned in accordance with the agreement that has been made along with the surplus value that may arise as a result of added value or interest. This is an obligation that must be fulfilled by the party who owes, but the party who provides the credit also has a handful of obligations that must be fulfilled as a form of accountability for the pawned goods that are received and maintained for a certain period of time, for example, maintaining the pawned goods from potential damage or carrying out maintenance so that the pawned goods function properly. However, the party who provides the credit has the right to receive compensation or a refund of the maintenance costs incurred to maintain the pawned goods; this is regulated in Article 1157, Paragraph 2, of the Civil Code, which is a guarantee for every entity that provides credit to obtain its rights or compensation from efforts to "rescue" the pawned goods.